A note on the method of harmonic balance - Dinh, Nguyen Van (Vietnam Journal of Mechanics, 2001)
Free oscillation period of the Duffing oscillator with cubic non-linearity was examined. A comparison between the exact period and those obtained by the asymptotic and the harmonic balance methods was done. It was shown that the remits given by the harmonic balance are acceptable even for large oscillations whereas the asymptotic method can only be applied for small oscillations.